Sensitivity to Flow Velocity Profiles in Electromagnetic Fowmeters with Various Magnetic Circuits - Virbalis, A. J.; Zebrauskas, S. (Elektronika ir Elektrotechnika, 1999)
The dependence of electromagnetic flowmeters electrode signal to parameters and form of magnetic circuit and to velocity distribution of fluid flow with axial symmetry in cross-section of pipe is computed using the program COSMOS 1.75M. The results of computation are discussed.